Services selection based on trust evolution and union for cloud computing - HU Chun-hua1; LIU Ji-bo1; LIU Jian-xun3 (Tongxin xuebao)
It was difficult for the service consumers to obtain high-quality composite services because of the existence of false or malicious service nodes in cloud computing environment.A novel cloud service-composition method based on the trust span tree was proposed.The trust relationship could be built after many times credible interaction between ser-vices requester and provider,and the trust union would be formed through the credible relationship evolution.So that the uncertain or malicious service should be excluded from the trust span tree,and the service composition would be carried out in a trust environment.At the same time,the measuring strategy of trust relationship among cloud services based on information entropy was designed,which could resolve the deficiencies of the trust parameter analysed by simply weighted angle in the previous studies.The experimental result shows that the method proposed in this paper is more su-perior in credibility and security,comparing to the traditional services selection methods.